2022
DOI: 10.3389/fmicb.2021.771527
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Correlates of Oral and Gut Microbiota in the Water Monitor Lizard, Varanus salvator (Laurenti, 1768)

Abstract: Numerous studies have demonstrated that food shapes the structure and composition of the host’s oral and gut microbiota. The disorder of oral and gut microbiota may trigger various host diseases. Here, we collected oral and gut samples from wild water monitor lizards (Varanus salvator) and their captive conspecifics fed with bullfrogs, eggs, and depilated chicken, aiming to examine dietary correlates of oral and gut microbiota. We used the 16S rRNA gene sequencing technology to analyze the composition of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 67 publications
4
10
0
Order By: Relevance
“…In this study, mealworm-fed geckos had higher gut microbial community diversity and richness although diet diversity was higher in wild geckos (Figure 2). That food diversity is not associated with gut bacterial alpha diversity in G. japonicus is similar to the findings demonstrated in V. salvator [31], Anser anser [57], and Ochotona curzoniae [58]. However, there are some species such as Gasterosteus aculeatus and Perca fluviatilis [59] and Fejervarya limnocharis [60] where gut microbial alpha diversity is negatively correlated with diet diversity.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…In this study, mealworm-fed geckos had higher gut microbial community diversity and richness although diet diversity was higher in wild geckos (Figure 2). That food diversity is not associated with gut bacterial alpha diversity in G. japonicus is similar to the findings demonstrated in V. salvator [31], Anser anser [57], and Ochotona curzoniae [58]. However, there are some species such as Gasterosteus aculeatus and Perca fluviatilis [59] and Fejervarya limnocharis [60] where gut microbial alpha diversity is negatively correlated with diet diversity.…”
Section: Discussionsupporting
confidence: 73%
“…There has been evidence that gut microbial compositions are closely correlated with food ingested by hosts [31] and with their sex [22]. In this study, mealworm-fed geckos had higher gut microbial community diversity and richness although diet diversity was higher in wild geckos (Figure 2).…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Previous studies on reptiles have shown that, for a given factor, it may affect the gut microbiota in some species but not in others. For instance, diet shapes the gut microbiota in S. crocodilurus [ 17 ] but not in the common water monitor Varanus salvator [ 31 ]. Compared with other reptile taxa, studies on gut microbiota in geckos have been limited, focusing only on the effects of fasting on gut microbiota in the common leopard gecko Eublepharis macularius [ 32 , 33 ] and the structure of gut microbiota in the common house gecko Hemidactylus frenatus [ 34 ].…”
Section: Introductionmentioning
confidence: 99%